PHENOMENOLOGICAL UNION IN THE FORMATION OF NEW PHENOMENAL CONCEPTS THROUGH PERCEPTIVE FILES, RELEVANCE, CAUSAL LINKS AND QUALIAS IN THE PHENOMENAL PHYSICAL COHESION OF EMPLOYABILITY IN THE EXPERIENCES WITNESSED - Jefferson, Jadir (Revista Gênero e Interdisciplinaridade, 2025)
The present study describes the possibility of “phenomenal unification” laws acting on a variety of phenomena acquired during experiences lived over time, capable of generating a new phenomenal concept through the files maintained in latent flow in the perceptive storage when exposed to the phenomenological unification processes by a sense of reference. Such references would assume a force of relevance through a correspondence with the contents of the property links, by the causal links and substantial knowledge that are part of the characteristics of the object in the experience. In addition, the sense of the force of relevance can be driven by a network of experienced sensations or qualia integrated into the context of related experiences that are fundamental for the formation of the new phenomenal meaning. Thus, we question whether the new phenomenological concepts would establish a physical-phenomenal cohesion with the other phenomenal concepts and their causal links that are in the same context of experience, even without a priori knowledge of the employability of this new concept.